Effect of alkaline hydrogen peroxide assisted with two modification methods on the physicochemical, structural and functional properties of bagasse insoluble dietary fiber - Luo, Mengying; Wang, Cheng; Wang, Chenshu; Xie, Caifeng; Hang, Fangxue; Li, Kai; Shi, Changrong (Frontiers in Nutrition, 2023)
Bagasse is one of major by-product of sugar mills, but its utilization is limited by the high concentration of lignin. In this study, the optimal alkaline hydrogen peroxide (AHP) treatment conditions were determined by the response surface optimization method. The results showed that the lignin removal rate was 62.23% and the solid recovery rate was 53.76% when bagasse was prepared under optimal conditions (1.2% H2O2, 0.9% NaOH, and 46 °C for 12.3 h), while higher purity of bagasse insoluble dietary fiber (BIDF) was obtained. To further investigate the modification effect, AHP assisted with high-temperature-pressure cooking (A-H) and enzymatic hydrolysis (A-E) were used to modify bagasse, respectively. The results showed that the water holding capacity (WHC), oil holding capacity (OHC), bile salt adsorption capacity (BSAC), and nitrite ion adsorption capacity (NIAC) were significantly improved after A-H treatment. With the A-E treatment, cation exchange capacity (CEC) and BSAC were significantly increased, while WHC, OHC, and glucose adsorption capacity (GAC) were decreased. Especially, the highest WHC, OHC, BSAC and NIAC were gained by A-H treatment compared to the A-E treatment. These changes in the physicochemical and functional properties of bagasse fiber were in agreement with the microscopic surface wrinkles and pore structure, crystallinity and functional groups. In summary, the A-H modification can effectively improve the functional properties of bagasse fiber, which potentially can be applied further in the food industry.